A Human-Specific Schizophrenia Risk Tandem Repeat Affects Alternative Splicing of a Human-Unique Isoform AS3MTd2d3 and Mushroom Dendritic Spine Density. (14th July 2020) - Cai, Xin; Yang, Zhi-Hui; Li, Hui-Juan; Xiao, Xiao; Li, Ming; Chang, Hong
Abstract: Recent advances in functional genomics have facilitated the identification of multiple genes and isoforms associated with the genetic risk of schizophrenia, yet the causal variations remain largely unclear. A previous study reported that the schizophrenia risk single-nucleotide polymorphism (SNP) rs7085104 at 10q24.32 was in high linkage disequilibrium (LD) with a human-specific variable number of tandem repeat (VNTR), and both were significantly associated with the brain mRNA expression of a human-unique AS3MT d2d3 isoform in Europeans and African Americans. In this study, we have shown the direct regulation of the AS3MT d2d3 mRNA expression by this VNTR through an in vitro minigene splicing assay, suggesting that it is likely a causative functional variation. Intriguingly, we have further confirmed that the VNTR and rs7085104 are significantly associated with AS3MT d2d3 mRNA expression in brains of Han Chinese donors, and rs7085104 is also associated with risk of schizophrenia in East Asians. Finally, the overexpression of AS3MT d2d3 in cultured primary hippocampal neurons results in significantly reduced densities of mushroom dendritic spines, implicating its potential functional impact. Considering the crucial roles of dendritic spines in neuroplasticity, these results reveal the potential regulatory impact of the schizophrenia risk VNTR on AS3MT d2d3 and provide insights into the underlying biological mechanisms.